Adaptive Fault-Tolerant H infinity Controller Design for Networked Systems with Actuator Saturation - Guan, Wei (Mathematical problems in engineering, 2013)
In this paper, an indirect adaptive fault-tolerant sub(H infinity ) controller design method is proposed for networked systems in the presence of actuator saturation. Based on the on-line estimation of eventual faults, the parameters of controller are being updated automatically to compensate the fault effects on systems. The designs are given in linear matrix inequalities (LMIs) approach, which can guarantee the disturbance tolerance level and adaptive sub(H infinity ) performances of networked systems in the cases of actuator saturation and actuator failures. An example is given to illustrate the efficiency of the design method.